2003
DOI: 10.1038/sj.ijo.0802462
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and blood pressure—results from the examination of 2365 schoolchildren in Germany

Abstract: OBJECTIVES: To investigate the relationship between different indices of body fat and blood pressure in children and adolescents. DESIGN: Cross-sectional cohort study along with regular public health service examinations in school classes two, five and nine. PARTICIPANTS: A total of 2365 healthy schoolchildren aged 8-16 y. MEASUREMENTS: Body mass index (BMI), skinfolds, waist-hip ratio, body fat determined by bioelectric impedance analysis and blood pressure. RESULTS: In comparison with recently published norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
2
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 23 publications
7
73
2
11
Order By: Relevance
“…Consequently, for many with high BP levels, measures directed at the long-term prevention of cardiovascular morbidity may need to be started in adolescence to achieve maximal effectiveness. Even though BMI and all the adiposity indices were found to be significantly associated with BP levels in both sexes, BMI and body fat mass showed the strongest association, most closely related to SBP in both genders and to DBP only in males, in agreement with the literature data indicating that BMI contributes significantly to BP variability (19)(20)(21)24,27,46) , even in non-obese subjects (24,25) . The correlation between parental and adolescents' BMI values supports previous findings (18,(54)(55)(56) showing an influence of both parents' BMI on their children.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Consequently, for many with high BP levels, measures directed at the long-term prevention of cardiovascular morbidity may need to be started in adolescence to achieve maximal effectiveness. Even though BMI and all the adiposity indices were found to be significantly associated with BP levels in both sexes, BMI and body fat mass showed the strongest association, most closely related to SBP in both genders and to DBP only in males, in agreement with the literature data indicating that BMI contributes significantly to BP variability (19)(20)(21)24,27,46) , even in non-obese subjects (24,25) . The correlation between parental and adolescents' BMI values supports previous findings (18,(54)(55)(56) showing an influence of both parents' BMI on their children.…”
Section: Discussionsupporting
confidence: 78%
“…In a sample of 2365 healthy schoolchildren aged 8-16 years, Reich et al (24) showed a significant trend towards a higher prevalence of hypertension in subjects with high BMI, but the positive correlation of hypertension to BMI was not only caused by overweight subjects. Indeed, when the high-risk group (above the 90th percentile) was excluded, the trend remained significant.…”
mentioning
confidence: 99%
“…98 As in adults, excessive visceral fat (central obesity) is associated with an increased disease risk in children and adolescents, particularly for components of the 'metabolic syndrome.' [9][10][11][12][13][14] The waist circumference measure, a proxy of visceral fat, is uniformly included in the diagnosis of the 'metabolic syndrome' in both children and adults. 99 Safe and effective treatments for central obesity in youth are urgently needed, given the increasing prevalence of overweight in youth, [1][2][3][4][5] and that the prevalence of 'metabolic syndrome' in overweight children and adolescents has been reported to be as high as 29-50%, 10,13 and rising.…”
Section: Central Obesitymentioning
confidence: 99%
“…Of major concern is the growing body of evidence reporting overweight-related morbidity in childhood and adolescence, both in the psychosocial [6][7][8] and physiological domain. [9][10][11][12][13][14] Recently, the prevalence of 'metabolic syndrome' was reported to be 39 and 50% in moderate and severely obese children and adolescents, respectively, indicating higher morbidity burden with greater obesity severity. 10 Unless this trend is curtailed, obesity-related disease, disability and death worldwide is projected to increase well into the 21st century, 15 whereas life expectancy at birth and at older ages may begin to decline by the middle of the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…Serum was stored at K20 8C until analysis of adiponectin concentrations. Two hundred and fiftynine healthy control subjects without diabetes and !21 years of age were recruited along with regular public health service examinations in pre-school and school classes from a study on anthropometric measurements ('Leipzig school children's project', (29)) and from referred children and adolescents or pre-operative visits to the paediatric outpatient clinic. To be included in the study, the control subjects had to be without any acute disease and without clinical conditions involving the endocrine-metabolic system.…”
Section: Subjectsmentioning
confidence: 99%